Failover Cluster Nodes and ISCSI Storage Area Network on Virtualization Windows Server 2016 - Abdullah, Mohammad Thoip; Qidri, Sulhan; Nuryadi, Wadi; Widianto, Septian Rheno (JOIN (Jurnal Online Informatika), 2020)
The use of data in this current digital era, the traditional model of connecting the storage media with servers, cannot meet the need for fast access to a very large amount of data. Storage Area Network can be the solution because this technology can handle a large amount of storage media (TeraByte), enable to be a share of storage resources, as well as giving data access in real-time, quick, and easy. Internet Small Computer System Interface (iSCSI) is a concept of storage media that use Internet Protocol as a medium for connecting storage media and data transfer through network service. Testing of availability server in this research use failover cluster technology, after testing done, then the result is obtained, when a failure or error occurs on the primary server, the primary server role will be automatically replaced by backup server with the same resource as the main server. As for the time automatic displacement server, when an active server makes failure, then it will only take less than 5 seconds. So, it can be concluded that this technology can minimize the value of the downtime in the system.